A comprehensive status, phylogenetic, and anatomical review of Stagnicola caperata (Say, 1829) in the south‐west United States. Issue 3 (14th December 2017) - Morningstar, Cayla R.; Inoue, Kentaro; Lang, Brian K.; Berg, David J.
Abstract: Freshwater gastropods are a major component of aquatic communities in arid regions. The isolation of aquatic habitats and poor dispersal abilities of organisms has resulted in the evolution of endemic species with small ranges. Human demands for water threaten the integrity of desert spring systems and as a result many freshwater snails from these regions are of conservation concern. One widespread lymnaeid species in North America, Stagnicola caperata (Say, 1829 ), exhibits distinct shell morphologies among populations in the south‐west United States. Because S. caperata is listed as endangered by the State of New Mexico owing to degradation of wetland habitats, accurate taxonomic assessment among populations is required in order to understand threats to the survival of this taxon. A holistic approach (morphometrics, phylogenetics, and reproductive anatomy) was used to investigate the taxonomic affinities of S. caperata in the south‐west United States by comparing these populations with topotypes. Morphometric analyses revealed similar levels of variation among populations, with large overlaps in shell morphologies. Both phylogenetic analysis and reproductive anatomy revealed the presence of two Stagnicola species in these populations: all populations except the Big Costilla Peak (BCP) population were referable to the nomen S. caperata, while BCP was Stagnicola cf. elodes . A total‐evidence approach that combines genetic and morphological data facilitates assessment of taxonomic affinities. The results provide conservation agencies with information necessary to detect species boundaries and then develop effective conservation and recovery plans for imperilled species.